Implementation of the Zenly Application as a Media for Monitoring Bhabinkamtibmas Performance in Preventing Crime in the Kuningan Police Legal Area - Gustriwidya, Dhea (Police Studies Review, 2024)
This research is motivated by the existence of Kuningan Police crime data based on total crime which shows an increase in cases from 2017 to 2019. This is of particular concern to the Kuningan police. Bhabinkamtibmas as a member of the National Police who is in direct contact with the target village has an important role in inviting the community to prevent criminal acts in the Kuningan Police jurisdiction. Technological developments have been utilized by the National Police to develop a system of reporting the results of activities in support of police performance by increasing oversight of the performance of Bhabinkamtimas. The technology can be accessed via a smartphone, the Zenly application. Therefore, a study was conducted with the aim of knowing how the implementation of the Zenly application as a media for monitoring the performance of Bhabinkatibmas in preventing criminal offenses in the Kuningan Police jurisdiction. The study was conducted with a qualitative approach, analytical descriptive research methods, and data collection techniques through interviews, observations, and document review. The results of the study were analyzed with several theories and concepts giving the conclusion that the application system of Zenly application needs to shape the work process to be more developed so that benefits can be felt by Bhabinkamtibmas and Kanit Binmas as supervisors of Bhabinkamtibmas performance in preventing crime. Based on the results of the study, it is recommended that the Binmas unit to get more support from the internal and external police in supporting the application of the Zenly application becomes much more useful for Bhabinkamtibmas so that its usefulness can be felt. In addition, it is also necessary to increase the quantity and quality of Bhabinkamtibmas personnel to be able to serve the community more optimally.